Effects of sputtering gas pressure dependence of surface morphology of ZnO films fabricated via nitrogen mediated crystallization. (12th December 2016) - Iwasaki, Kazuya; Matsushima, Koichi; Yamashita, Daisuke; Seo, Hyunwoong; Koga, Kazunori; Shiratani, Masaharu; Itagaki, Naho
ABSTRACT: ZnO films were fabricated by RF magnetron sputtering with nitrogen mediated crystallization (NMC) under various gas pressures. X-ray diffraction measurements show that the NMC-ZnO films are highly crystalline regardless of the gas pressure, and the full width at half maximum values of the (0002) rocking curves range from 0.032 to 0.044°. In contrast, atomic force microscopy (AFM) reveals that the gas pressure plays an important role in determining the surface morphology of the films. The root-mean-square (RMS) roughness decreases monotonically from 1.05 to 0.60 nm with increasing pressure from 0.2 to 0.7 Pa. However, the RMS roughness increases with further increases in the pressure, reaching 2.15 nm at 2.1 Pa. The height distribution of the NMC-ZnO films derived from the AFM images is narrowest at 0.7 Pa, indicating that the smooth surface obtained at 0.7 Pa can be attributed to spatially uniform nucleation occurring in a short time period. These results indicate that the sputtering gas pressure is a key parameter for controlling the surface morphology of NMC-ZnO films.